Natural Resource Extraction in the Interior: Scouts, Spirits and Chinese Loggers in the Forests of Northern Mozambique. Issue 3 (3rd May 2020) - Nielsen, Morten; Bunkenborg, Mikkel
Abstract : In their search for precious hardwood in the forests of northern Mozambique, Chinese logging companies employ locals with knowledge of the forest to scout for trees. Known as olheiros, these tree scouts are indispensable to both Chinese and Mozambican participants in the industry, but, strangely, they are also regarded with scepticism and sometimes even hostility from both sides. Based on ethnographic fieldwork among Mozambicans and Chinese involved in the local logging industry of Cabo Delgado in northern Mozambique, this article traces the social and cultural ramifications of natural resource extraction in a rural environment that is currently undergoing radical changes. We begin the article by discussing the economic and political transformations brought about by opening up the local logging industry to foreign agencies. By outlining the genealogy and increased importance of the olheiro figure, we then move to examine the cosmological implications of this intensified form of resource extraction in a rural universe. Acquiring new skills and capacities working for Chinese companies, many olheiros are seen as embodying Chinese spirit forces and, along with locating hardwood, they are assigned the task of mediating between Chinese and local spirit worlds. In a context where logging companies operate largely unchecked by state agents and often collude with local elites, however, the hunt for hardwood has affected local communities in ways that cannot be repaired by the untrained ritual efforts of the olheiros .